Matérialités instables, Temporalités complexes. Stimulantes schizophrénies numériques - Emmanuel Doutriaux (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This paper discusses the design of the project - using collaborative modeling tools - based on the experience of Philippe Gazeau’s architecture agency, which will have experienced the transition from manual work to Cao and Bim. “If with this environment you save time, you also give more time - confide the architects”. This apparent gap is questioned here. When, on the one hand, by being subject to upstream information, the project would tend to desert its floating cosa mentale nature in order to switch very quickly to trivial formalizations - from another point of view, the increase in data and the interoperability of formats would allow, by engaging the project in the field of infinite simulations, to delay any objective stability. How can we think of these antagonistic temporalities ? What can we say about the material conditions to which they are committed ?